2019
DOI: 10.1016/j.smallrumres.2019.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The determination of treatment effect of chitosan oligosaccharide in lambs with experimentally cryptosporidiosis

Abstract: In this study, it was aimed to investigate the efficacy of chitosan oligosaccharide administrations in different doses of experimental infected lambs with Cryptosporidium parvum. 32 male lambs were used in the study and the lambs were divided into 4 groups with 8 lambs in each group. Groups 1, 2 and 3, twice a day, were administered chitosan oligosaccharide at a dose of 100, 500, and 1000 mg/kg for 7 days, respectively, with milk replacer. In group 4, lambs with cryptosporidiosis were subjected to normal feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The immune modulation role of COS via material intervention may assist in protection against gastrointestinal parasites and infectious diseases. A recent study indicated that COS can have a positive effect on both clinical signs and on stool character in lambs experimentally infected with cryptosporidiosis, and can reduce oocyst excretion [ 17 ]. However, the detailed molecular mechanisms of how maternal COS supplements regulate the immune system of lambs need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The immune modulation role of COS via material intervention may assist in protection against gastrointestinal parasites and infectious diseases. A recent study indicated that COS can have a positive effect on both clinical signs and on stool character in lambs experimentally infected with cryptosporidiosis, and can reduce oocyst excretion [ 17 ]. However, the detailed molecular mechanisms of how maternal COS supplements regulate the immune system of lambs need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, COS has an antibacterial effect on infectious diseases, such as cryptosporidiosis. [ 17 ]. The oral administration of COS at doses of 100, 500 and 1000 mg/kg for 7 d significantly reduced oocyst excretion in experimentally induced cryptosporidiosis in lambs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan, a natural linear polysaccharide has also been investigated for efficacy in C. parvum infected lambs. Therapeutic treatment after the onset of disease improved clinical signs and fecal consistency, and reduced oocyst excretion, but did not eliminate cryptosporidiosis completely in treated lambs ( Aydogdu et al., 2019 ).…”
Section: Treatment Options In Humans and Animals: The Past And Curren...mentioning
confidence: 99%
“…Researchers have suggested various modes of action of polysaccharides such as cyclodextrins and chitosan in controlling viral, bacterial, and parasitic infections that involve use of their antimicrobial properties, osmotic properties, and cholesterol-sequestering ability, among others ( Aydogdu et al., 2019 ; Braga, 2019 ). It is likely that, in the case of Cryptosporidium , these polysaccharides might form a protective film over the intestinal surface due to their adhesive properties, which may act as a physical barrier and prevent cell invasion by parasites.…”
Section: Treatment Options In Humans and Animals: The Past And Curren...mentioning
confidence: 99%